"I had to surpress just a few words in one sentence, and was surprised ... at my accuracy": intertextuality as a tool to reconstruct the past in "Levels of Life", by Julian Barnes - Martínez Gómez, Mirna del Carmen (Tropelías: Review of Literary Theory and Comparative Literature, 2025)
In this article, the main focus is the intertextual references the narrator uses as a means to reconstruct his past while, at the same time, tries to communicate and understand his loss, brought about by the sudden death of his wife. I analyze the quotes and explore the effects the texts read by the narrator have on his understanding and the process with which those texts are resignified. Due to the text’s nature and the way in which the narrator handles the quoted fragments, it is possible to question the traditional separation between author and narrator.